Rotavirus NSP4114-135 peptide has no direct, specific effect on chloride transport in rabbit brush-border membrane - Vasseur Monique; Lorrot Mathie (Virology Journal, 2006)
Abstract The direct effect of the rotavirus NSP4114-135 and Norovirus NV464-483 peptides on 36Cl uptake was studied by using villus cell brush border membrane (BBM) isolated from young rabbits. Both peptides inhibited the Cl-/H+ symport activity about equally and partially. The interaction involved one peptide-binding site per carrier unit. Whereas in vitro NSP4114-135 caused nonspecific inhibition of the Cl-/H+ symporter, the situation in vivo is different. Because rotavirus infection in young rabbits accelerated both Cl- influx and Cl- efflux rates across villi BBM without stimulating Cl- transport in crypt BBM, we conclude that the NSP4114-135 peptide, which causes diarrhea in young rodents, did not have any direct, specific effect on either intestinal absorption or secretion of chloride. The lack of direct effect of NSP4 on chloride transport strengthens the hypothesis that NSP4 would trigger signal transduction pathways to enhance net chloride secretion at the onset of rotavirus diarrhea.